Nearly Reversible ECG Steganography based on Polar Coordinate System with Digital Replacement Technique - YANG, CHING YU; Huang, Chi-Kai (Transactions on Engineering and Computing Sciences, 2021)
In this paper, we present a nearly reversible data hiding for electrocardiogram (ECG) hosts. Based on the polar coordinate system domain, medical diagnosis and personal data can be embedded in an ECG signal by the simple digital replacement technique. Simulations revealed that the restored ECG with near lossless quality can be obtained by the proposed method at receiver site. In addition, the perceived quality of the marked ECG is very good with a high payload size. Moreover, the resultant signal-to-noise ratio (SNR), peak SNR, and payload of the proposed method outperforms those of existing techniques. Since the computation cost is low, the proposed method can be used in portable biometrics or ECG measuring instruments.